Genes, medicine, and you - Silverstein, Alvin; Silverstein, Virginia B. (Hillside, N.J., U.S.A. : Enslow, 1989)
Describes how advances in genetics are being used in screening and counseling and discusses the medical and ethical aspects of genetic engineering.
Includes index.
Bibliography: p. 154-155.
Booklist.
School Library Journal.
Wilson's Junior High School.
8.3
Keywords: Medical genetics -- Juvenile literature; Genetic engineering; Medical genetics; Genetic engineering; Medical genetics